Digital game-based learning: C++ / Rachael Voo Sze Ying - Rachael, Voo Sze Ying (2000)
Game-based learning has been recognized as an important alternative to traditional method of teaching. It can help both adults and children in learning new concepts, gaining expertise and practicing knowledge. Though game-based learning is mostly applied in children's education, it can be helpful for adult vocational and university-level learning. Digital Game-based Learning: C++, which I prefer to refer to as Digital Game-based C++ Learning System is a web-based system that promotes learning C++ through games. It is the first of its kind whereby no programming language is to be learned through games. So, basically this system's objective to provide aid in learning basic concepts of procedural programming, enhance learner's understanding of procedural programming and motivate learner to be more interested in teaming C++ programming language. It targets especially students or learners who are currently learning programming using C++ language and they felt that they need extra help in understanding the concepts of C++ programming.